40r+48s=

Simple and best practice solution for 40r+48s= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 40r+48s= equation:


Simplifying
40r + 48s = 0

Solving
40r + 48s = 0

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '-48s' to each side of the equation.
40r + 48s + -48s = 0 + -48s

Combine like terms: 48s + -48s = 0
40r + 0 = 0 + -48s
40r = 0 + -48s
Remove the zero:
40r = -48s

Divide each side by '40'.
r = -1.2s

Simplifying
r = -1.2s

See similar equations:

| 9r^2-49=0 | | -6(8+4n)+5(1+4n)=-11 | | 5(b-4)=12 | | -6(8+4n)+5(1+4n)=-1 | | p+.33p=.67 | | 41*8.98= | | 2r^2+7r^2-2r^2= | | x^2-x-14=3x-2 | | 3x+34-x+3=1 | | 8(5k-4)+3(-8k-6)=30 | | 2x^2+16x+42=0 | | 7(2-x)=5x | | 4x^7-20x^6+8x^5=0 | | 8(y-2)+6=2(y+1) | | x^2+6x+13=5 | | 3(2x-4)=3 | | 3w^2+12w+30=0 | | 12(7c+2)= | | Solvey=2x-3 | | x^2+2x=-10 | | 6.7x-4+3x-1.9= | | 0.5(2x+8)=5 | | ln(x+2)+ln(x+1)=0 | | 5g-5-8-5g= | | 16(3-d)=-4 | | 5x+6=6x-1 | | 7x-7y=49 | | 155=-31m | | (b)(b)+14b=0 | | 2x^2+(2t+1)x+t=0 | | x^2-40-6x=0 | | 20s^2-16s=48 |

Equations solver categories